2017
DOI: 10.7150/thno.19358
|View full text |Cite
|
Sign up to set email alerts
|

Blood Droplet-Based Cancer Diagnosis via Proteolytic Activity Measurement in Cancer Progression

Abstract: Matrix metalloproteinase (MMP) is a key marker and target molecule for cancer diagnosis, as MMP is able to cleave peptide chains resulting in degradation of extracellular matrix (ECM), a necessary step for cancer development. In particular, MMP2 has recently been recognized as an important biomarker for lung cancer. Despite the important role of detecting MMP molecules in cancer diagnosis, it is a daunting task to quantitatively understand a correlation between the status of cancer development and the secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The present study demonstrated that an increase in the plasma level of MMP2 after treatment was significantly associated with the efficacy of anti‐PD‐1 therapy. Since MMP2 has been shown to have a key role in degradation of the extracellular matrix, it is possible that an increase in MMP2 after anti‐PD‐1 therapy might accelerate lymphocyte migration to tumor nests. MMP2 is known to be produced by stromal or tumor cells in the tumor microenvironment, but the changes in the plasma MMP2 level were not positive correlation with those in tumor burden (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that an increase in the plasma level of MMP2 after treatment was significantly associated with the efficacy of anti‐PD‐1 therapy. Since MMP2 has been shown to have a key role in degradation of the extracellular matrix, it is possible that an increase in MMP2 after anti‐PD‐1 therapy might accelerate lymphocyte migration to tumor nests. MMP2 is known to be produced by stromal or tumor cells in the tumor microenvironment, but the changes in the plasma MMP2 level were not positive correlation with those in tumor burden (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a nanomechanical biosensor to measure active MMP-2 has been developed using a cantilever biosensor that detects molecular processes on its surface, producing a change in its deflection fluctuations or resonant frequency ( Choi et al, 2017 )., The biosensor surface was modified with 3-aminopropyltrimethoxysilane and functionalized with PEGylated peptides linked to the sequence GPLGVRGK that contains the cleavage site for MMP-2. The biosensor is installed in a fluid cantilever holder that quantifies MMP-2 in small amounts of fluid samples.…”
Section: Matrix Metalloproteinases’ Contribution To Cancer Diagnosis ...mentioning
confidence: 99%
“…Proteases are classified into families based on their catalytic site, i.e., aspartic, cysteine, glutamic, metallo, serine, and threonine proteases [ 1 ]. They are involved in numerous intracellular and extracellular processes and are known to play an important role in cancer [ 2 , 3 , 4 , 5 ], cardiovascular disease [ 6 , 7 ], pancreatitis [ 8 , 9 ], diabetes [ 10 ], viral infections [ 11 ] (including the novel COVID-19 [ 12 ]), and microbial [ 13 , 14 ] infections. Almost 6% of the proteins in the human genome are proteases [ 15 ], and they can be found in biological fluids like saliva [ 16 ], serum [ 17 ], and urine [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%